Faktor Penyebab Keterlambatan Pengajuan Klaim Pasien BPJS Rawat Inap di Rumah Sakit Umum Daerah Soe - Honcy Ernesta Nomeni; Rina Waty Sirait; Yoseph Kenjam (Universitas Nusa Cendana, 2020)
Problems commonly found in submitting insurance claims are incomplete documents, follow-up claims, the mismatch of the rates submitted by the hospital with the INA-CBGs rates or those paid by BPJS Kesehatan, irregularities in the coding of disease diagnoses, and the delay in claiming payments by BPJS Kesehatan. Based on the preliminary study at Soe Public Hospital in October 2019, there were still several administrative problems in submitting claims for JKN program. It was proven by the fact that there were still patients with JKN who did not bring a copy of their BPJS Kesehatan cards and the referral letter determined by BPJS Kesehatan when registering for a treatment. The aim of this study is to determine the factors causing the delay in submitting claims for inpatients with BPJS at Soe Public Hospital in 2020.This was a qualitative descriptive study. The population in this study was staff who are directly involved in the insurance claiming process. The sample was selected using purposive sampling technique that consisted of one assembling staff, one coding staff, two internal verifiers and one BPJS Kesehatan verifier. The results of the study indicated that the process of submitting claims for patients with BPJS Kesehatan by Soe Public Hospital did not carry out in a comprehensive and integrated manner because of incomplete medical record status, lack of coordination and teamwork between staff who record medical status that involves assembling staff, coding staff, and hospital verifier. This made a delay in submitting claims for inpatients with BPJS Kesehatan. There were also other obstacles found in the process of submitting claims for inpatients with BPJS Kesehatan at Soe Public Hospital. It is suggested that hospital managers need to evaluate staff who are responsible for submitting claims for inpatients with BPJS Kesehatan regularly and to assess the strengths and weaknesses of each staff.